PKM Pelatihan dan Pendampingan Perhitungan Harga Pokok Produksi dan Pengelolaan Keuangan Serta Peningkatan Penjualan Menggunakan Digital Marketing - Rahmadani; Nurhaflah Soraya; Sondang Beatrix Siahaan; Muhammad Asrin Jazuli; Tasya Melati Sulaiman; Dara Anisa; Muhammad Fatih Asykarillah Nasution; Ahmad Luthfi Munawar; Muhammad Yuan Aunhanief; Andini Aura Fachrani (JURPIKAT (Jurnal Pengabdian Kepada Masyarakat), 2024)
This community service program aims to solve partner problems related to improving Partners' ability to calculate production costs and simple financial reports. In addition, this PKM activity also provides products to MSMEs in the form of simple programs based on MS. Excel so that it is easier for partners to solve their accounting problems. Another problem that is solved is about the use of technology, namely related to marketing through digital by utilizing social media, marketplaces. This PKM is important for partners to improve their business again and will ultimately be able to increase sales through expanding market share by adding customers by utilizing digital marketing. The targeted output is to improve partner capabilities so that partners become more independent and able to improve financial management, especially in setting production costs that are in accordance with standards and ultimately increasing business sales along with increasing profits and improving the welfare of MSME actors.